Introduction of laparoscopic abdominal aortic aneurysm repair. Issue 4 (March 2015) - Howard, A. Q.; Bennett, P. C.; Ahmad, I.; Choksy, S. A.; Mackenzie, S. I. P.; Backhouse, C. M.
<x xml:space="preserve">Abstract</x> Background The aim was to review a consecutive series of patients treated with laparoscopic abdominal aortic aneurysm (AAA) repair. These patients were compared with patients having elective open AAA repair. Methods Demographic and operative details were collected prospectively and outcomes recorded for all patients undergoing laparoscopic or open AAA repair. Results A total of 316 patients underwent laparoscopic (51), open (53) or endovascular (EVAR; 212) AAA repair between 2007 and 2013. The median age of patients who had laparoscopic or open repair was 72 (i.q.r. 66–75) years, and 92·3 per cent were men. There was no significant difference in sex distribution, age or V‐POSSUM physiology score between laparoscopic and open repair. Of the 51 laparoscopic procedures, six were totally laparoscopic, 43 were laparoscopically assisted and two were converted to open repair. Pain scores were similar on days 1 and 3 after laparoscopic and open repair, even though epidurals were used in the open group, and were lower on days 5 and 7 after laparoscopic procedures. Patients who had laparoscopic repair had significantly fewer postoperative cardiorespiratory and renal complications (P = 0·017), and were discharged from hospital sooner (median 5 (i.q.r. 3–7) versus 8 (6–11) days; P = 0 ·001). Conclusion Laparoscopic AAA repair was performed safely, and with at least equivalent outcomes to open repair, in patients unfavourable for EVAR.